1997
DOI: 10.1128/mcb.17.7.3850
|View full text |Cite
|
Sign up to set email alerts
|

Ras Links Growth Factor Signaling to the Cell Cycle Machinery via Regulation of Cyclin D1 and the Cdk Inhibitor p27KIP1

Abstract: Activation of growth factor receptors by ligand binding initiates a cascade of events leading to cell growth and division. Progression through the cell cycle is controlled by cyclin-dependent protein kinases (Cdks), but the mechanisms that link growth factor signaling to the cell cycle machinery have not been established. We report here that Ras proteins play a key role in integrating mitogenic signals with cell cycle progression through G 1 . Ras is required for cell cycle progression and activation of both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
307
3
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(338 citation statements)
references
References 48 publications
20
307
3
8
Order By: Relevance
“…The H322 cell line used in this study has a wild type ras. The ras protein has also been reported to be involved in the regulation of cyclin D1 and the CDK inhibitor, p27 KIP1 (Aktas et al, 1997). Pathways downsteam of ras are involved in cellular responses to stress.…”
Section: Discussionmentioning
confidence: 99%
“…The H322 cell line used in this study has a wild type ras. The ras protein has also been reported to be involved in the regulation of cyclin D1 and the CDK inhibitor, p27 KIP1 (Aktas et al, 1997). Pathways downsteam of ras are involved in cellular responses to stress.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the signals from Ga 12/13 are translated into growth-promoting signals by the small GTPases Ras, Rac, and Rho. It has been reported that Ras, Rho, Rac, and CDC42 play an essential role in cell cycle progression from G1 to S phase (Aktas et al, 1997;Takuwa and Takuwa, 1997;Olson et al, 1995;Hirai et al, 1997). An additional role for Rac in progression from G2 to M phase has been also identi®ed (Moore et al, 1997).…”
Section: Ga 12/13 : the Gep Oncogenes?mentioning
confidence: 99%
“…In general, oncogenic Ras subverts mitogenic signaling in the process of mediating transformation. Specifically, Ras utilizes signaling through the MEK/ERK pathway to stimulate cyclin D1 expression/function (Filmus et al, 1994;Aktas et al, 1997;Crespo and Leon, 2000). It has been shown that oncogenic transformation through Ras in cell culture and animal models is dependent on cyclin D1 (Liu et al, 1995;Peeper et al, 1997).…”
Section: Introductionmentioning
confidence: 99%